2015 Nordic Circuits and Systems Conference (NORCAS): NORCHIP &Amp; International Symposium on System-on-Chip (SoC) 2015
DOI: 10.1109/norchip.2015.7364364
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Power monitoring for self-aware embedded systems

Abstract: Dynamic Thermal and Power Management methods require efficient monitoring techniques. Based on a set of data collected by sensors, embedded models estimate online the power consumption: this task is a real challenge, since models must be both accurate and low cost, but they also have to be robust to variations. In this paper, we investigate a self-aware approach using the performance events and the external temperature. We present a solution (PESel) for the selection of the relevant information. This method is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Commercial ultra-low power (ULP) microcontrollers integrate trace modules or Performance Monitoring Units (PMU). This method allows real-time and accurate performance and power evaluations [5] [6]. The monitor output can be used to evaluate architecture bottlenecks during applications execution (e.g., miss rates).…”
Section: Related Workmentioning
confidence: 99%
“…Commercial ultra-low power (ULP) microcontrollers integrate trace modules or Performance Monitoring Units (PMU). This method allows real-time and accurate performance and power evaluations [5] [6]. The monitor output can be used to evaluate architecture bottlenecks during applications execution (e.g., miss rates).…”
Section: Related Workmentioning
confidence: 99%
“…Power models are still generated like for a standard evaluation flow, with low-level hardware simulations, manufacturers' design kits and literature. It has been demonstrated that using Performance Monitoring Counters (PMC) can be used for power consumption estimation [10], [11]. Because, inside a bloc, some signals/events are more correlated with the bloc's power consumption than other ones, it is possible to use a simplified power model based on these events, which will be captured thanks to a dedicated activity monitor.…”
Section: Evaluation Flowmentioning
confidence: 99%
“…If PMUs are great tools for software optimization, they can also be used for adaptive behaviours. [5] demonstrates how it is also possible to create a power monitor by using a PMU and a power model of the processor. However, the number of hardware counters is limited and the available events are centred on the processor.…”
Section: Introduction and Related Workmentioning
confidence: 99%